Pit Lakes Affected by a River Contaminated with Brines Originated from the Coal Mining Industry: Evolution of Water Chemistry in the Zakrzówek Horst Area (Krakow, Southern Poland) - Jacek Motyka; Kajetan d’Obyrn; Ondra Sracek; Adam Postawa; Michał Źróbek (Energies, 2022)
Long-term coal mining activities in the Upper Silesia significantly affect the environment in southern Poland. Discharges of brines (with TDS reaching over 110 g/L) from mines are the main source of pollution of many rivers in Poland, including the Vistula River. The Zakrzówek horst is a small geological structure composed of the Upper Jurassic limestones. These limestones were exploited in several quarries. In the largest one (the “Zakrzówek” quarry), exploitation reached the depth of 36 m below the water table, i.e., about 32 m below the average water level in Vistula River which flows 700 m from the quarry. An important part of this inflow into quarries came from the contaminated Vistula River, with a chloride concentration over 2 g/L. The exploitation ceased in 1991, and dewatering ended in 1992. In the old quarry area, pit lakes appeared, which are unique because they present an example of a post-mining site affected by the riverine water contaminated with brines. Investigations of physicochemical parameters of water in the Zakrzówek area were carried out in the period of 1990–2020. Results showed that the largest pit lake was initially meromictic with a distinct stratification. After several years, holomictic conditions developed due to the surface layer freshening and convective mixing.